Evaluation of progressive collapse behavior in reinforced concrete buildings. (November 2022) - Vinay, M.; Kodanda Rama Rao, P.; Dey, Subhashish; Swaroop, A.H.L.; Sreenivasulu, Anduri; Venkateswara Rao, K.
Abstract: Progressive collapse is a catastrophic chain reaction of failure of a structure that is caused due to loss of vertical load bearing element of the structure, resulting damage of a part of the structure or entire structure. In our research work 10 storey regular Reinforced Concrete framed structure is considered and is seismically designed with IS 1893:2016 in SAP2000 version 20 modeling. The different column removal scenarios both in plan and elevation suggested by guidelines were examined by alternate load path method using nonlinear staged construction available in the software and then identify the potential of the structure to withstand progressive collapse. Numerical results were compared by analyzing columns and beams separately by calculating demand capacity ratios and the requirement of percentage of steel for failed structural elements are predicted both in flexure and shear stresses. Our objective is to provide clear conceptual step-by-step descriptions of various procedures for progressive collapse analysis 3D (three-dimensional) Finite Element Methods (FEM) and non-linear static push-down analysis in SAP2000 software was used to assess the progressive collapse potential of a typical gravity-load designed mid-rise reinforced concrete building with open ground floor. The beam is actually designed to resist the shear force up to 39.84 kN. So in order to resist the shear failure we need to provide enough vertical reinforcement. The failed structural elements were re-designed to resist progressive collapse in order to satisfy the acceptance criteria recommended by the guidelines. It's showed that the incorporation of perimeter beams in buildings improved the progressive collapse resistance as it reduces joint displacement and chord rotation at column removal locations by providing sufficient stiffness and load paths for increased gravity loads. The study results can be used to develop and calibrate the nonlinear numerical model for analyzing high-rise building progressive collapse behavior and can help provide information that may improve new and existing reinforced concrete core-wall building robustness against progressive collapse.